2021
DOI: 10.1021/acs.macromol.1c01100
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conductivities of Broad Dispersity Lithium Salt-Doped Polystyrene/Poly(ethylene oxide) Triblock Polymers

Abstract: We describe the impact of center polyether segment dispersity (Đ = M w/M n ∼ 1.45) on the ionic conductivities of lithium salt-doped polystyrene-block-poly­(oligo­(ethylene oxide) carbonate)-block-polystyrene (bSOS) electrolytes with narrow dispersity end blocks. Three bSOS samples with M n,total = 11.7–23.9 kg/mol were doped with lithium bis­(trifluoromethanesulfonyl)­imide (LiTFSI) with r = [Li+]/[EO units] = 0.09. Small-angle X-ray scattering (SAXS) analyses reveal that these samples with f O/salt = 0.55–0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
1
2
0
Order By: Relevance
“…To elucidate the potential of the polymers to be applied as electrolytes the DC conductivity was investigated by broadband dielectric spectroscopy (BDS). As shown in Figure 3 a the low-molecular-weight POIL-2 showed a higher conductivity compared to the high-molecular-weight POIL-3 , matching the conclusions that—in line with expectations—low-molecular-weight POILs generally offer higher conductivity [ 25 , 26 , 27 , 28 ]. When 4% UPy moieties were introduced into the polymer backbone ( CPILU-5 ), the conductivity was barely influenced by the non-conductive UPy moieties as compared to the homopolymer POIL-2 (see red squares for POIL-2 and blue triangles for CPILU-5 in Figure 3 a).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…To elucidate the potential of the polymers to be applied as electrolytes the DC conductivity was investigated by broadband dielectric spectroscopy (BDS). As shown in Figure 3 a the low-molecular-weight POIL-2 showed a higher conductivity compared to the high-molecular-weight POIL-3 , matching the conclusions that—in line with expectations—low-molecular-weight POILs generally offer higher conductivity [ 25 , 26 , 27 , 28 ]. When 4% UPy moieties were introduced into the polymer backbone ( CPILU-5 ), the conductivity was barely influenced by the non-conductive UPy moieties as compared to the homopolymer POIL-2 (see red squares for POIL-2 and blue triangles for CPILU-5 in Figure 3 a).…”
Section: Resultssupporting
confidence: 82%
“…While many POILs have been reported predominantly with polyimidazolium ions [ 17 , 21 ] or other POILs [ 18 , 22 , 23 ] as self-healing electrolytes, poly-pyrrolidinium-based self-healing electrolytes have been scarcely reported, despite the fact that pyrrolidinium-based ionic liquids generally have a higher electrochemical stability [ 24 ]. Moreover, in many publications POILs were synthesized via free radical polymerization, which offers no control over the molecular weight of POILs, thus yielding polymers with a broad polydispersity and a poor reproducibility, which significantly influences the final conductivity of the obtained polymer electrolytes [ 25 , 26 , 27 , 28 ]. While UPy was widely exploited in polymers synthesized via RAFT polymerization [ 29 , 30 , 31 ], only a few [ 32 ] RAFT kinetics studies regarding an acrylate-based UPy monomer were reported, let alone studies involving its copolymerization with ionic monomers.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high crystallinity of PEO below the melting temperature ( T m,PEO ≈ 62 °C for 10–20 kg/mol) leads to a significant reduction in conductivity near room temperature . There have been numerous studies focused on disrupting crystallinity in PEO using PEO-grafted polymethacrylates , and PEO-based copolymers. For instance, poly­( oligo -oxyethylene methyl ether methacrylate) (POEM), with its ether-oxygen side chains, is promising in terms of significantly improved room-temperature conductivity vs analogous salt-doped PEO systems when the appropriate side-chain lengths are employed. , Other approaches also have been developed to decrease the crystallinity of PEO, including nanoparticle addition, polymer blending, , and cross-linking. Additionally, small-molecule plasticization and low- T g segment introduction have been shown to accelerate segmental relaxation, and polymer architecture modification can effectively alter the Li + -polymer coordination , and/or the Li + solvation-site connectivity. , Although improved overall conductivities have been achieved, the significant anion motion in these PEO-based electrolytes results in low t Li+ s (≈0.2) , and therefore relatively modest Li + conductivities (∼10 –4 S/cm at 60–100 °C).…”
Section: Introductionmentioning
confidence: 99%